Synthesis and evaluation of novel benzimidazole derivatives as potential anti bacterial and anti fungal agents. Issue 1 (1st January 2021) - Pardeshi, Vishwajeet Amarsingh; Pathan, Sultan; Bhargava, Amit; Chundawat, Narendra Singh; Singh, Girdhar Pal
ABSTRACT: The novel analogs of the heterocyclic compound benzimidazole were synthesized by alkylation with different small alkylating groups. The antibacterial and antifungal activities of different synthesized benzimidazole compounds has been assessed with a zone of inhibition by well diffusion method, which has shown good activity. The synthesized molecules were subjected to molecular docking studies with a crystal structure of cytochrome P450 14 alpha-sterol demethylase (CYP51) coming through Mycobacterium tuberculosis in composite with fluconazole was collected from PDB ID: 1EA1 and molecular docking research work holding up the antifungal activity exhibiting inhibition and binding energy.